2017
DOI: 10.18632/oncotarget.16270
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of P4HA1 inhibits neovascularization via targeting glioma stem cell-endothelial cell transdifferentiation and disrupting vascular basement membrane

Abstract: Emerging evidence has demonstrated transdifferentiation process of glioma stem cells (GSCs) into endothelial cells (ECs) in glioma neovascularization. Herein, we focused on screening for genes that were differentially expressed in the transdifferentiation process using microarray analysis. Bioinformatics analysis revealed differential expression of the prolyl 4-hydroxylase subunit alpha-1 (P4HA1) gene. We determined that P4HA1 expression was correlated with histological grade, the level of Ki67 and microvessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
(46 reference statements)
1
36
0
Order By: Relevance
“…In prognosis-related GMPSs network, gene P4HA1 was a key node with highest degree. The previous study has reported that P4HA1 was the active catalytic component of prolyl 4-hydroxylase in cancers [28], glioma [29], prostate cancer [30] and pancreatic cancer [31], P4HA1 can promote chemoresistance, tumor growth and metastasis. The prognosis-related gene CD53 could form a MGPS with P4HA1 in OS patients.…”
Section: Discussionmentioning
confidence: 98%
“…In prognosis-related GMPSs network, gene P4HA1 was a key node with highest degree. The previous study has reported that P4HA1 was the active catalytic component of prolyl 4-hydroxylase in cancers [28], glioma [29], prostate cancer [30] and pancreatic cancer [31], P4HA1 can promote chemoresistance, tumor growth and metastasis. The prognosis-related gene CD53 could form a MGPS with P4HA1 in OS patients.…”
Section: Discussionmentioning
confidence: 98%
“…In our analyses of primary melanoma tumors, both the tumor cells and the stromal fibroblasts produced P4HA1, although the tumor cells appeared to be the main producers. Also in other cancers, such as gliomas and prostate cancer, P4HA1 staining has mostly been reported in the tumor cells (Chakravarthi et al , ; Zhou et al , ). This is interesting, as fibroblasts are considered the main producers of collagens, which are the most important substrates for P4HA1.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of P4HA1 has been reported to inhibit cancer cell proliferation in vitro and reduce tumor growth in xenograft models of breast and prostate cancer and gliomas (Chakravarthi et al , ; Gilkes et al , ; Zhou et al , ). In our melanoma model, the silencing of P4HA1 did not appear to interfere with tumor cell proliferation in vitro or in vivo , as assessed by staining with the cell proliferation marker Ki‐67 .…”
Section: Discussionmentioning
confidence: 99%
“…To establish intracranial orthotopic tumour models, mice were anaesthetised with isoflurane and stabilized in a stereotactic apparatus (KOPF, USA). Then, a total of 2 × 10 4 GL261 cells were injected into the right striatum (1.8 mm medio‐lateral, 0.8 mm anterior‐posterior, and 3 mm dorso‐ventral) as previously described . The secondary injection of S. aureus or BV2 cells was given at the same location.…”
Section: Methodsmentioning
confidence: 99%
“…Then, a total of 2 × 10 4 GL261 cells were injected into the right striatum (1.8 mm medio-lateral, 0.8 mm anterior-posterior, and 3 mm dorso-ventral) as previously described. 16,17 The secondary injection of S. aureus or BV2 cells was given at the same location.…”
Section: Bacterial Strains and Culturementioning
confidence: 99%